Persistence of poverty among the Badjaos of Bongao, Tawi-Tawi, ARMM, Philippines - Usman, Kuraiza; Baconguis, Rowena DT. (2016)
The study sought to understand the persistence of poverty among the Badjao people in Tawi-Tawi, Autonomous Region of Muslim Mindanao (ARMM), Philippines. Considered the poorest in their communities, badjaos are Sea Gypsies of Sulu and Celebes seas who are scattered in different coastal areas in Mindanao. Specifically, the study aimed to determine the educational background, psychological outlook, economic, nutrition and health conditions, political and social capabilities, and access to government services of the Badjaos. These factors are referred to as conditions that facilitate or hinder mobility in society. Thus, their absence can further bind people in a state of poverty or what is referred to as deprivation trap. Semi-structured questionnaires were used to investigate the socio-economic conditions of the respondents. Two gate helped the researchers identity the respondents based in their availability and willingness to discuss their situations. The selected research sites were two villages in Bongao, Tawi-Tawi, which are known as Badjao communities. Results showed that respondents suffer from a deprivation trap, a condition that keeps people in poverty. A model for program implementation that is guided by collaboration, networking and cultural sensitivity is proposed. Program of the proposed model focus on informative, persuasive, participatory and formative interventions.
Keywords: Indigenous peoples; Poverty; Badjaos (Philippine people)